MINORITIES’ RIGHTS FROM ISLAMIC SOCIO-POLITICAL PERSPECTIVE: EXPLORATION OF MADĪNAH CHARTER AND CONSTITUTION OF PAKISTAN - Saeed, Riaz Ahmad; Tahir, Muhammad; Akhter, Naseem; Abdul Rashid, Hafiz (Journal of Al-Tamaddun, 2020)
This study aims to explore the historical role of Methāq-e-Madīnah (Charter of Madīnah) for the rights of minorities and its association with the Constitution of the Islamic Republic of Pakistan, 1973. The rights of minorities have been the most burning issues in human history. In recent decades, the contemporary socio-political system has put considerable attention on minorities’ issues globally. In this scenario, for the Muslim world, the charter has become the first official historical treaty document, which owned minorities’ rights, respect, and identity. This divinely inspired charter was designed under the political wisdom of the Holy Prophet Muhammad (S.A.W.) on 1st AH/624 CE. The charter had been declared Madῑnah a federal capital, which provided equal opportunities and benefits to Muslims and non-Muslims. Before this treaty document, human history could not bring any example regarding the rights of religious minorities. The Charter presents certain principles and rules for peaceful coexistence and harmonious society between Muslims and other minorities. It provides a social model of peace and prosperity focusing on religious and political freedom of humanity. The agreement provided equal rights, religious autonomy and socio-cultural freedom to the communities of Madῑnah including Jews, Christians, and polytheists. This study attempts to demonstrate how the charter of Madῑnah can be perceived as a preamble for peaceful coexistence between Muslims and non-Muslims in a contemporary pluralistic world in general and Pakistan in particular. The present study suggests the protection and care of minorities’ rights from the perspective of the charter of Madῑnah. This paper adopts historical, analytical, and comparative qualitative research methodology.